2015
DOI: 10.1002/ase.1545
|View full text |Cite
|
Sign up to set email alerts
|

Actual drawing of histological images improves knowledge retention

Abstract: Medical students have to process a large amount of information during the first years of their study, which has to be retained over long periods of nonuse. Therefore, it would be beneficial when knowledge is gained in a way that promotes long-term retention. Paper-and-pencil drawings for the uptake of form-function relationships of basic tissues has been a teaching tool for a long time, but now seems to be redundant with virtual microscopy on computer-screens and printers everywhere. Several studies claimed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
2
33
0
1
Order By: Relevance
“…Early anatomists such as Andreas Vesalius employed drawing as a means of observation and recording the findings of their explorations of the anatomy through dissection (Saunders and O’Malley, ). The positive effect of drawing on learning generally (Coates, ; Adams, ; Alkaslassy and O’Day, ; Weekes, ), in medical students (Bardes et al, ; Rodenhauser et al, ; Shapiro et al, ; Coles et al, ; Barsom et al, ) and specifically in the learning of anatomy has already been well described (Flannery, ; Phillips, ; Nayak and Kodimajalu, ; Ranaweera and Montplaisir, ; Moore et al, ; Clavert et al, ; Backhouse et al, ; Balemans et al, ). In a randomized, blinded, and controlled study of 416 medical students, Alsaid and Bertrand () showed statistically significant improvements in memorization of an anatomical region after one and seven weeks, as a result of drawing before and after a dissection session.…”
Section: Introductionmentioning
confidence: 99%
“…Early anatomists such as Andreas Vesalius employed drawing as a means of observation and recording the findings of their explorations of the anatomy through dissection (Saunders and O’Malley, ). The positive effect of drawing on learning generally (Coates, ; Adams, ; Alkaslassy and O’Day, ; Weekes, ), in medical students (Bardes et al, ; Rodenhauser et al, ; Shapiro et al, ; Coles et al, ; Barsom et al, ) and specifically in the learning of anatomy has already been well described (Flannery, ; Phillips, ; Nayak and Kodimajalu, ; Ranaweera and Montplaisir, ; Moore et al, ; Clavert et al, ; Backhouse et al, ; Balemans et al, ). In a randomized, blinded, and controlled study of 416 medical students, Alsaid and Bertrand () showed statistically significant improvements in memorization of an anatomical region after one and seven weeks, as a result of drawing before and after a dissection session.…”
Section: Introductionmentioning
confidence: 99%
“…Art and drawing, despite their long established history with the teaching and learning of anatomy, had received relatively few literature to describe its efficacy within the medical education at recent times [21,22]. This historic link can often be symbolized by Leonardo Da Vinci's Vitruvian Man (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing also has the benefit of a vast history of anatomical illustration that culturally supports the popularity of this method (Ghosh, 2015). Drawing has received relatively greater attention in terms of primary research in anatomy education that other artistic methods, with several recent studies investigating the benefits of this particular technique (Ainsworth, Prain, & Tytler, 2011;Backhouse et al, 2017;Balemans, Kooloos, Donders, der Zee, & Catharina, 2016;Lyon et al, 2013;Naug, Colson, & Donner, 2011;Nayak & Kodimajalu, 2010). Learning through drawing has also been investigated in terms of educational neuroscience and cognitive processing (Chamberlain et al, 2014;Guérin, Ska, & Belleville, 1999) and has certain theoretical underpinnings (Petherbridge, 2010).…”
Section: Tip 2: Choose Your Artistic Methods Wiselymentioning
confidence: 99%